Penentuan Premi Asuransi Jiwa Berjangka Status Last Survivor Menggunakan Model GFGM-Type II Copula - Peni Erawati; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2022)
The last survivor status of term life insurance is multiple life insurance whose benefits are paid by the insurance company to the heirs if all policyholders have died within a predetermined period of time. The risk of death of a married couple is usually assumed to be independent of each other. But in fact there is a relationship between the risk of death for the couple. The method that can be used to determine the premium for married couples with the assumption of independence is the GFGM-Type II Copula method. The purpose of this study is to determine the formulation of the last survivor term life insurance premium using the GFGM-Type II Copula method. The results obtained from this study are the formulation of the last survivor term life insurance premium using the GFGM-Type II Copula method. Based on the simulation results, it is concluded that the last survivor term life insurance premium calculated with the assumption of independence is smaller than using GFGM-Type II copula Copula.